Identification of Off-Patent Compounds That Present Antifungal Activity Against the Emerging Fungal Pathogen Candida auris - de Oliveira, Haroldo Cesar; Monteiro, Maria Candida; Rossi, Suélen Andreia; Pemán, Javier; Ruiz-Gaitán, Alba; Mendes-Giannini, Maria José Soares; Mellado, Emilia; Zaragoza, Oscar (Frontiers in Cellular and Infection Microbiology, 2019)
Candida auris is an emerging fungal pathogen of great concern among the scientific community because it is causing an increasing number of hospital outbreaks of difficult management worldwide. In addition, isolates from this species frequently present reduced susceptibility to azole and echinocandin drugs. For this reason, it is necessary to develop new antifungal strategies to better control the disease caused by this yeast. In this work, we screened drugs from the Prestwick chemical library, which contains 1,280 off-patent compounds that are already approved by the Food and Drug Administration, with the aim of identifying molecules with antifungal activity against C. auris. In an initial screening, we looked for drugs that inhibited the growth of three different C. auris strains and found 27 of them which it did so. Ten active compounds were selected to test the susceptibility profile by using the EUCAST protocol. Antifungal activity was confirmed for seven drugs with MICs ranging from 0.5 to 64 mg/L. Some of these drugs were also tested in combination with voriconazole and anidulafungin at sub inhibitory concentrations. Our results suggest synergistic interactions between suloctidil and voriconazole with fractional inhibitory concentration index (FICI) values of 0.11 to 0.5 and between ebselen and anidulafungin (FICI, 0.12 to 0.44). Our findings indicate that drug repurposing could be a viable alternative to managing infections by C. auris.